INTERNATIONAL PRACTICE OF BANK DOUBTFUL ASSETS MANAGEMENT - Vasylchenko, Zoya (Journal of European Economy, 2017)
The paper studies the international practice of doubtful assets management in banking establishments and determines the role of the state in overcoming banking crises.